Rational Fabrication of Anti‐Freezing, Non‐Drying Tough Organohydrogels by One‐Pot Solvent Displacement. Issue 22 (27th April 2018) - Chen, Fan; Zhou, Dan; Wang, Jiahui; Li, Tianzhen; Zhou, Xiaohu; Gan, Tiansheng; Handschuh‐Wang, Stephan; Zhou, Xuechang
Abstract: Tough hydrogels, polymeric network structures with excellent mechanical properties (such as high stretchability and toughness), are emerging soft materials. Despite their remarkably mechanical features, tough hydrogels exhibit two flaws (freezing around the icing temperatures of water and drying under arid conditions). Inspired by cryoprotectants (CPAs) used in the inhibition of the icing of water in biological samples, a versatile and straightforward method is reported to fabricate extreme anti‐freezing, non‐drying CPA‐based organohydrogels with long‐term stability by partially displacing water molecules within the pre‐fabricated hydrogels. CPA‐based Ca‐alginate/polyacrylamide (PAAm) tough hydrogels were successfully fabricated with glycerol, glycol, and sorbitol. The CPA‐based organohydrogels remain unfrozen and mechanically flexible even up to −70 °C and are stable under ambient conditions or even vacuum. Abstract : Anti‐freezing, non‐drying tough organohydrogels are fabricated by a solvent displacement strategy. Water molecules in the hydrogels are partially displaced by cryoprotectants, as inspired by the cryopreservation of biological samples. This method opens a way to rationally tune the freezing and drying tolerance for many water‐based hydrogels.